A comparison of multi-component systems approaches to suicide prevention. (April 2018) - Baker, Simon TE; Nicholas, Jennifer; Shand, Fiona; Green, Rachel; Christensen, Helen
Objective: To describe the new Australian approach to suicide prevention, LifeSpan, and compare it to other multi-component intervention models. Method: The components, implementation strategies and effectiveness of three multi-component intervention models are described and compared in a narrative review. Results: The LifeSpan, European Alliance Against Depression (EAAD), and Zero Suicide models emphasise the provision of evidence-based interventions and continuity of care. Only LifeSpan and EAAD include community-based interventions at the population level, and LifeSpan is the only model to include school-based interventions. Zero Suicide focuses on healthcare settings. Implementation of LifeSpan and EAAD involves the convening of multi-stakeholder teams at the local level. To date, there is some, albeit mixed, evidence in support of EAAD, while LifeSpan and Zero Suicide await further evaluation. Conclusions: Although multi-component approaches to suicide prevention share similar components, there are some important differences. Multiple interventions implemented at the same time and tailored to the local community context are likely to be the most effective way of reducing the rate of suicide. There is growing evidence for the effectiveness of multi-component systems approaches to suicide prevention; however, further evaluation is required.